"A place without peace is no place at all": Violence, fear, and the Paz do Senhor in Mozambique. Issue 3 (July 2021) - Howell, Alan Byron; Montgomery, Robert Andrew
Peace is a central idea in the culture of the Makua-Metto people, as well as in Paul's letter to the Ephesians. This article looks at the important role of peace and the language of peace in connection with rootedness in a place. If "a place without peace is no place at all, " then what Mozambique needs is the Paz do Senhor for real reconciliation. In adopting the greeting of Paz do Senhor, the church is articulating a hope (evident in the book of Ephesians) that there is a true and lasting peace to be found for a place like Mozambique.